2019
DOI: 10.1007/s11606-019-04902-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record Use in Internal Medicine Clerkships and Sub-internships for Medical Students Graduating from 2012 to 2016

Abstract: BACKGROUND: As electronic health records (EHRs) became broadly available in medical practice, effective use of EHRs by medical students emerged as an essential aspect of medical education. While new federal clinical documentation guidelines have the potential to encourage greater medical student EHR use and enhance student learning experiences with respect to EHRs, little is known nationally about how students have engaged with EHRs in the past. OBJECTIVE: This study examines medical student accounts of EHR us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Many of them have shown that most students access EHRs while they are in medical school. [4][5][6][7][8][9][10] This is not surprising given the widespread use of EHR systems in clinical settings and calls to incorporate instruction in EHR competencies early in a physician's education. Studies also suggest, however, that some medical students receive limited opportunities to enter information, including notes and orders, into patient records in EHRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them have shown that most students access EHRs while they are in medical school. [4][5][6][7][8][9][10] This is not surprising given the widespread use of EHR systems in clinical settings and calls to incorporate instruction in EHR competencies early in a physician's education. Studies also suggest, however, that some medical students receive limited opportunities to enter information, including notes and orders, into patient records in EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also suggest, however, that some medical students receive limited opportunities to enter information, including notes and orders, into patient records in EHRs. [4][5][6][7][8][9][10] This tends to occur despite their ability to access them generally.…”
Section: Introductionmentioning
confidence: 99%
“…In another large survey of around 16,600 graduating medical students, 84% had entered information of some type into the EMR on their internal medicine clerkship or subinternship; however, 43% had never entered admission orders [6]. Yet students are expected to step into residency on July 1 and care for patients, including night shifts and with varying degrees of supervision and support.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent survey, fewer than 10% of students on their obstetrics clerkship had entered orders and less than half (47%) had written a history and physical note in the patient chart [ 5 ]. In another large survey of around 16,600 graduating medical students, 84% had entered information of some type into the EMR on their internal medicine clerkship or subinternship; however, 43% had never entered admission orders [ 6 ]. Yet students are expected to step into residency on July 1 and care for patients, including night shifts and with varying degrees of supervision and support.…”
Section: Introductionmentioning
confidence: 99%
“…The recent changes announced by CMS regarding medical student documentation in patient records have put a spotlight on this complex and often fractious relationship between the health system and medical education. Wallach et al 2 provide important context to how medical students are utilizing the electronic health record and raise key questions about training and residency preparedness. As we move more towards competency-based, objectively measured outcomes in medical education, Stratton et al 3 warn that even the best intentioned, learner-centered curriculum may be subsumed by organizationally centered forces, and that we should not lose the educational value of an activity in the quest to find measurable outcomes valued by the health system.…”
mentioning
confidence: 99%